(untitled) - Hugh-Jones, E. M. (Oxford, 1969)
Technology, technical change, innovation are strictly different concepts, but with sufficient overlap to justify the measure of interchangeability in their use to be found in these papers.
Keywords: Technological innovations,Economic development,Đổi mới công nghệ,Phát tiển kinh tế